Pharmacological approaches to the treatment of obstructive sleep apnoea. - Kohler, M; Bloch, K; Stradling, J (2009)
BACKGROUND: Currently the treatment of choice for symptomatic obstructive sleep apnoea (OSA) is continuous positive airway pressure (CPAP). Some patients with OSA do not tolerate CPAP or have insufficiently severe symptoms to justify its use; for these patients, drug therapy would be a desirable potential therapeutic alternative. OBJECTIVE: To summarize the current evidence on the effectiveness of drug therapy in patients with OSA. METHODS: A systematic review of randomized controlled trials was performed to investigate the effects of drug therapy on OSA. RESULTS/CONCLUSIONS: Searches of bibliographical databases revealed 33 trials investigating the effects of 27 different drugs on OSA severity and/or symptoms. The mechanisms by which these drugs are supposed to improve OSA include, amongst others, an increase in tone of the upper airways, an increase in ventilatory drive, a reduction in airway resistance, and alterations in surface tension forces in the upper airway. In most of these studies there was no significant effect on OSA observed. However, there is evidence from a few small trials that some drugs, especially those thought to increase upper airway muscle tone, have the potential to reduce OSA severity; but further data from larger studies of adequate duration are needed.